2015
DOI: 10.1038/bjc.2015.179
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic review and meta-analysis of immunohistochemical prognostic biomarkers in resected oesophageal adenocarcinoma

Abstract: Background:Oesophageal adenocarcinoma (OAC) is one of the fastest rising malignancies with continued poor prognosis. Many studies have proposed novel biomarkers but, to date, no immunohistochemical markers of survival after oesophageal resection have entered clinical practice. Here, we systematically review and meta-analyse the published literature, to identify potential biomarkers.Methods:Relevant articles were identified via Ovid medline 1946–2013. For inclusion, studies had to conform to REporting recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 116 publications
1
15
0
2
Order By: Relevance
“…A higher expression of P53, HER2, and GLUT1 has individually been shown to be associated with a worse survival in esophageal adenocarcinoma [19]. However, there have been a variety of other cancers which have been investigated with a similar methodology.…”
Section: Introductionmentioning
confidence: 99%
“…A higher expression of P53, HER2, and GLUT1 has individually been shown to be associated with a worse survival in esophageal adenocarcinoma [19]. However, there have been a variety of other cancers which have been investigated with a similar methodology.…”
Section: Introductionmentioning
confidence: 99%
“…The fraction of Ki67‐positive tumor cells (Ki67 labeling index, Ki LI) has been proven to be an established prognostic marker for various tumor types, especially in breast cancer (Hu et al ., ; Li et al ., ). Previous studies have shown a strong linear correlation between Ki‐67 labeling index and esophageal adenocarcinoma development (McCormick Matthews et al ., ). However, the prognostic significance of Ki67 expression in ESCC remains inconclusive.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies that attempted to identify clinically applicable predictive biomarkers for treatment response or overall prognosis have often been underpowered or included heterogeneous patient populations with squamous cell carcinoma and adenocarcinoma. Biomarker analysis can also be hampered by different neoadjuvant treatments in advanced OAC, making comparisons between studies difficult.…”
Section: Discussionmentioning
confidence: 99%